Proses Morfologis pada Bahasa Madura: Studi pada Mahasiswa Madura di Universitas Trunojoyo - Irfan Irwiandi; Mixghan Norman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: Morphological Processes in the Madurese Language: A Study in Madurese Students at Trunojoyo University. Researchers aim to know the morphological processes that exist in the Madurese language and as a learning medium for the next generation. This research uses a descriptive qualitative research method using data collection techniques by communicating directly and observing the speech of Trunojoyo Madura University students. The results showed that morphological p roses are the process of word formation that goes through the process of affixation (Affixation), the process of twisting (Duplication) and komposition in the M language adura the morphological process is only a process of affixation and duplication.